2005
DOI: 10.1051/0004-6361:20053049
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared imaging of active galaxies

Abstract: Abstract. High resolution, mid-infrared (MIR) images of nine nearby active galaxies are presented. The data were obtained with the TIMMI 2 instrument mounted at the ESO 3.6 m telescope using a set of N-band narrow filters. The resulting images have an angular resolution of 0.6 −1 . The MIR emission has been resolved in four galaxies: NGC 253, NGC 1365, NGC 1808 and NGC 7469. The images show a circumnuclear population of unknown MIR sources in NGC 1365 and NGC 1808, coincident with radio sources. These MIR/radi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
163
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(187 citation statements)
references
References 69 publications
21
163
2
1
Order By: Relevance
“…Millimeter/sub-millimeter and mid-IR high spatial resolution observations of the nuclear region of NGC 1068 support the classical picture of a rotating torus (e.g., Tacconi et al 1994;Schinnerer et al 2000;Galliano et al 2005;Poncelet et al 2007). However, in some previous works (e.g., Schinnerer et al 2000) it was speculated that the classical (large-scale) molecular torus is not always needed to explain the occultation of the nuclear regions.…”
Section: Structure Of the Cnd And Limitations Of The Modelmentioning
confidence: 55%
“…Millimeter/sub-millimeter and mid-IR high spatial resolution observations of the nuclear region of NGC 1068 support the classical picture of a rotating torus (e.g., Tacconi et al 1994;Schinnerer et al 2000;Galliano et al 2005;Poncelet et al 2007). However, in some previous works (e.g., Schinnerer et al 2000) it was speculated that the classical (large-scale) molecular torus is not always needed to explain the occultation of the nuclear regions.…”
Section: Structure Of the Cnd And Limitations Of The Modelmentioning
confidence: 55%
“…flip from near-to mid-IR wavelengths, with the factor ∼2.5 increase in spatial resolution providing a more accurate and consistent result. Galliano et al (2003Galliano et al ( , 2005 We discount directly observed synchrotron radiation from the radio jet accounting for the polarization, as an extrapolation of the radio emission to the mid-IR provides too little flux. Hence, these data confirm that the extended mid-IR polarized emission north of the nucleus is mostly from dust in the ionization cone.…”
Section: Discussionmentioning
confidence: 99%
“…For NGC 1365, Sakamoto et al (2007) found five CO hot spots with line widths (FWHM) between 60 and 90 km s −1 that seem to be associated with SSCs of ∼10 6 M (Galliano et al 2005). Hsieh et al (2011) found many GMAs in the molecular ring (14 GMAs) and the dust lane (5 GMAs) of NGC 1097.…”
Section: Gmas In Galaxies With Nuclear Molecular Ringsmentioning
confidence: 97%